Effect of Sub-Lethal Concentration of Iron on Growth and Survival of Daphnia (Müller, 1785) - Kumar, Kanchan; Tiwari, V. K.; Dube, Kiran; Prakash, Chandra; Babitha Rani, A. M.; Verma, A. K. (Fishery Technology, 2020)
In the present study the effect of iron on growth andsurvival of Daphnia (Müller, 1785) has been studied.Neonates of Daphnia were exposed to differentwater-borne iron concentrations. Although iron istoxic at high concentrations, they are also essentialelements required for many biological processes.Iron is a vital metal for Daphnia for normaldevelopment and reproduction. Mass culture ofDaphnia has been done in plastic tubs. Duringexperiment, the effects of iron on Daphnia werestudied at an exposure equivalent to the 48 h LC50.Based on the LC50, seven Fe2+ levels (preparedthrough serial dilution from a stock solution of5 mgL-1) for the chronic toxicity tests were selected.These were 0, 0.25, 0.50, 1.00, 2.00, 4.00 and 8.00 mgL-1of Fe2+. The population density of Daphniaincreased with increase of sub-lethal dosages of ironand decreased significantly at higher toxic dosages,indicating that iron is required as micronutrients forstimulating growth in terms of population density.